Divergent adaptation to Qinghai-Tibetan Plateau implicated from transciptome study of Gymnocypris dobula and Schizothorax nukiangensis. (April 2017) - Yu, Mengchao; Zhang, Dongsheng; Hu, Peng; Peng, Sihua; Li, Weiwen; He, Shunping; Zhai, Wanying; Xu, Qianghua; Chen, Liangbiao
Abstract: The Schizothoracine fishes are widely distributed in the Qinghai-Tibetan Plateau (QTP) area and its peripheral regions, which provide a prime example of adaptation in highland aquatic environments. Recent progresses have revealed various genetic adaptations of these fishes by comparing to distantly related lowerland species, however, comparative studies on closely-related species of different altitudes are still lacking. In this study, we sequenced and annotated a primitive Schizothoracine fish Schizothorax nukiangensis Tsao and a highly specialized one Gymnocypris dobula . We performed evolutionary analyses to investigate the candidate genes and signaling pathways involved QTP highland adaptation in both Schizothoracine fishes. Analysis of the 11, 007 one-copy orthologs to the primitive cyprinid species, Danio rerio, revealed that both G. dobula and S. nukiangensis showed elevated evolutionary rates. A large number of genes related to hypoxia, including genes involved metabolic processes and cardiovascular system development, exhibited signatures of positive selection in both Schizothoracine fishes, but very few positively selected genes were found overlapping among these Schizothoracines. Our results indicated divergent genetic adaptation to highland environment for aquatic species living in QTP. Highlights: The evolutionary rates of the schizothoracines were accelerated in relative to zebrafish. Divergent genetic adaptation was detected in the schizothoracines endemic to different altitudes. Multiple positive selection genes related to hypoxia were identified.